Pengaruh Perbedaan Jenis Umpan Terhadap Hasil Tangkapan Pada Alat Tangkap Huhate (Pole And Line) di Perairan Misool Selatan Kepulauan Raja Ampat - Melisa Masengi; Dwi Indah Widaya Yanti; Stevi Kunu (Lembaga Penelitian dan Pengabdian, Universitas Kristen Papua, 2022)
The operation of the pole and line fishing gear is very dependent on the availability of live bait and also some fishing aids used to support the operation of the fishing gear. Pole and line is a type of fishing gear consisting of a fishing rod, fishing line and non-linking hooks. The purpose of this study was to determine the type of bait that has the most influence on pole and line catches. The research was conducted in March-April 2020 in South Misol, Raja Ampat Regency. The method used is coefisien method. The results showed that the different types of white castle bait and black castle bait in this study affect the number of catches. This can be seen in the catch of the white castle bait 65% and the black castle bait 35%. The results showed that using pole and line fishing gear with white castle live bait is better used.